Circulating plasma levels of miR-106b-5p predicts maximal performance in female and male elite kayakers - Torres-Aguilera, I.; Pinto-Hernandez, P.; Iglesias-Gutierrez, E.; Terrados, N.; Fernandez-Sanjurjo, M. (Frontiers in Sports and Active Living, 2023)
Introduction: Plasma miR-106b-5p levels have been described as an exercise performance predictor in male amateur runners, although no information is available about female athletes. The aim of this study was to analyze the predictive value on sports performance of plasma miR-106b-5p levels in elite female and male kayakers at the beginning and at the end of a training macrocycle, as well as the potential underlying molecular mechanisms using an in silico approach.